2015
DOI: 10.1016/j.mefs.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Potential predictors for successful misoprostol treatment for early pregnancy failure: Clinical and color Doppler imaging study

Abstract: Objective: To identify the clinical characteristics and features of color Doppler imaging related to successful misoprostol treatment for early pregnancy failure.Design: Prospective observational study. Main outcome measures: Factors related to successful misoprostol treatment for early pregnancy failure.Materials and methods: Four groups of women with early pregnancy failure (missed, anembryonic and incomplete miscarriage) were included in the study. The first group included 159 cases, 73 were presenting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Lower gestational age was significantly associated with success rate (increased gestational age decrease success rate). Our finding agree with another study showed that the lower gestational age the higher success rate of misoprostol [14] .…”
Section: Discussionsupporting
confidence: 93%
“…Lower gestational age was significantly associated with success rate (increased gestational age decrease success rate). Our finding agree with another study showed that the lower gestational age the higher success rate of misoprostol [14] .…”
Section: Discussionsupporting
confidence: 93%
“…Another study concluded that women with active vaginal bleeding and/or abdominal colic in the 24 hours before misoprostol administration, nulliparas, and women with low blood flow in trophoblastic tissue were most likely to have complete miscarriage. 30 Unfortunately, Doppler studies were not performed on our participants.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…ELkholi and Hefeda worked on identifying the potential predictors of the successful medical management of first trimester miscarriage 18 in a prospective observational study and found that active vaginal bleeding and/or localized abdominal colic in the 24 hours preceding misoprostol administration, as potential predictors of the success of medical management with misoprostol. But according to the Aubert Agostini and his co-workers 19 , parity was the only predictor for the successful medical management.…”
Section: Discussionmentioning
confidence: 99%